2011
DOI: 10.1111/j.1600-0501.2011.02288.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histologic and histomorphometric evaluation of socket preservation using a synthetic nanocrystalline hydroxyapatite in comparison with a bovine xenograft: a randomized clinical trial

Abstract: Socket preservation using either NCHA or DBBM in combination with collagen membrane, results in similar, limited horizontal ridge width alterations following tooth extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 27 publications
5
113
1
3
Order By: Relevance
“…An additional method is by observing volumetric changes using 3D Imaging Techniques. A common adjunct to this approach is the histological evaluation of bone core samples, because cellular activity is not revealed by imaging techniques [32][33][34]. Although cone-beam computed tomography (CBCT) provides a 3-dimensional image of bone volume and topography, and generates data of higher accuracy, sensitivity, reliability, and precision than periapical radiography [35][36][37], this technology was not available for us at the start of the study.…”
Section: Discussionmentioning
confidence: 98%
“…An additional method is by observing volumetric changes using 3D Imaging Techniques. A common adjunct to this approach is the histological evaluation of bone core samples, because cellular activity is not revealed by imaging techniques [32][33][34]. Although cone-beam computed tomography (CBCT) provides a 3-dimensional image of bone volume and topography, and generates data of higher accuracy, sensitivity, reliability, and precision than periapical radiography [35][36][37], this technology was not available for us at the start of the study.…”
Section: Discussionmentioning
confidence: 98%
“…These days the use of HA is limited, and is more used for bone defects fillings (e.g. ;after tooth extraction) (43,44,45) .…”
Section: A Ceramicmentioning
confidence: 99%
“…Many reports agreed that socket grafting preserve the socket from collaps and better than nongrafted socket or normal healing socket. [4][5][6][7] Other studies found that covering the grafted socket with collagen membrane or soft-tissue graft give better result than uncover grafted or nongrafted socket in the term of the amount of bone formation. 6,8 As the collagen membrane try to preserve the blood clot, maintain the space and preventing soft-tissue migration into the socket.…”
Section: Introductionmentioning
confidence: 99%